precal!

Prove: (3cosx + 4sinx)^2 + (4cosx - 3sinx)^2=5 ...this is all under the square root sign.

I get 9cos^2x + 16sin^2x +16cos^2x + 9sin^2x

now i know that sin^2 equals 1-cos^2....so would that be 9cos^2x + 17-cos^2x+16cos^2+ 10cos^2x? if not please help..and if this is correct..what would come after this step?


continuing from your left side you had:

9cos^2x + 16sin^2x +16cos^2x + 9sin^2x

this is ok so far.

group this into 9(sin^2 x + cos^2 x) + 16(sin^2 x + cos^2 x)
which is 9(1) + 16(1), because sin^2 x + cos^2 x = 1

So the left side is 25
You said that there was a square root over everything?
so...., how about that!

  1. ๐Ÿ‘ 0
  2. ๐Ÿ‘Ž 0
  3. ๐Ÿ‘ 72
asked by linds

Respond to this Question

First Name

Your Response

Similar Questions

  1. PRECAL!

    Prove: (3cosx + 4sinx)^2 + (4cosx - 3sinx)^2=5 ...this is all under the square root sign. this is what i did please check. i multipied both binomials. but i get cos square x..and sincosx ..how do i combine them..please help! In

    asked by just on March 27, 2007
  2. math

    Here's my question: Determine if each system has one, two, or no solutions. (Show your work - 3 marks each) a)y=2x^2-2x+1 and y=3x-5 b)y=x^2+3x-16 and y=-x^2-8x-18 Here's my work on the question: a) x=(-b plus/minus sign (square

    asked by Alex on January 26, 2015
  3. Math simplifying mixed radicals

    Please help me simplify these following mixed radicals:: and show me how you did it cause I need to learn : I don't know how to type a square root sign so I just wrote square root and the numbers infront of the square root are

    asked by Miley on September 14, 2013
  4. calculus please help me

    Let f(x)=9sinx/2sinx+4cosx. Then 'f(x)= ((2sinx+4cosx)(9cosx)-(9sinx)(2cosx-4sinx))/(2sinx+4cosx)^2. The equation of the tangent line to y=f(x) at a=2 can be written in the form y=mx+b where m= 9and b= ______.?????

    asked by Leslie on May 7, 2008
  5. Calculus exam review, PLEASE HELP!!

    for each function, determine the equation of the tangent line to the graph for the indicated value of the variable. a) y = 3cosx + 4sinx + 1 , when x = pie b) y = x - 3cosx , when x = (5pie)/3

    asked by stephanie on June 21, 2012
  6. Pre Calculus

    Prove that 2/square root 3cosx-sinx=sec(pi/6-x)

    asked by Nathan on April 22, 2010
  7. Math/Algebra HELP

    Can you please check these answers: 1. If the first Now= -9, which equation represents this sequence? -9, -4, 1, 6, 11 A. Next= Now -5 B. Next= Now + 5 C. Next= 5* Now -1 D. Next= 5* Now + 1 Answer: A 2. Which inequality statement

    asked by Snoopy on April 18, 2009
  8. Algebra

    Rationalize each expression by building perfect nth root factors for each denominator. Assume all variables represent positive quantities. I donโ€™t understand how to compute these. Also I donโ€™t have the square root sign so I

    asked by Becca on January 18, 2013
  9. Math simplifying mixed radicals

    Please help me simplify these following mixed radicals:: and show me how you did it cause I need to learn : I don't know how to type a square root sign so I just wrote square root: 2 square root 48 3 square root 81 6 square root

    asked by Miley on September 14, 2013
  10. Algebra

    When you're breaking down the square root in the quadratic formula into several parts- say it was the originally the square root of 80 so you break it down to square root of 4 and square root of 20-would the results be added or

    asked by Peter on October 5, 2009

More Similar Questions